Posterior Reversible Encephalopathy Syndrome due to High Dose Corticosteroids for an MS Relapse. (26th May 2015) - Morrow, Sarah A.; Rana, Robina; Lee, Donald; Paul, Terri; Mahon, Jeffrey L.
Abstract : Increased blood pressure is a known adverse effect associated with corticosteroids but little is published regarding the risk with the high doses used in multiple sclerosis (MS). A 53-year-old female with known relapsing remitting MS presented with a new brainstem relapse. Standard of care treatment for an acute MS relapse, 1250 mg of oral prednisone for 5 days, was initiated. She developed an occipital headache and dizziness and felt generally unwell. These symptoms persisted after treatment was complete. On presentation to medical attention, her blood pressure was 199/110 mmHg, although she had no history of hypertension. MRI changes were consistent with posterior reversible encephalopathy syndrome (PRES), demonstrating abnormal T2 signal in both thalami, the posterior occipital and posterior parietal white matter with mild sulcal effacement. As her pressure normalized with medication, her symptoms resolved and the MRI changes improved. No secondary cause of hypertension was found. This is the first reported case of PRES secondary to high dose corticosteroid use for an MS relapse without a history of hypertension and with no other secondary cause of hypertension identified. This rare complication should be considered in MS patients presenting with a headache or other neurological symptoms during treatment for a relapse.